MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) - Henny Sukmawati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
Learning through the problem-based learning approach is a series of learning activities that are expected to empower students to become an independent individual and be able to face every problem encountered in his life. Problem-based learning is innovation in learning, this is because in problem-based learning students' thinking abilities can be optimized through systematic group work processes so students can hone, test and develop their thinking abilities on an ongoing basis. In application of problem-based learning requires the readiness of teachers and students to be able to collaborate in solving problems raised. The teacher must be ready to be a mentor as well as a tutor for students who can provide motivation and help students to master problem solving skills. For teachers, an understanding of various student-centered approaches, one of which is problem-based learning needs to be improved to face the challenges of life now and in the future.